2018
DOI: 10.17814/mechanik.2018.10.165
|View full text |Cite
|
Sign up to set email alerts
|

Forces modeling in a surface peripheral grinding process with the use of various design of experiment (DoE)

Abstract: Title of article: "Modelowanie sił w szlofowaniu obwodowym płaszczyzn według różnych planów badawczych" (" Forces modeling in a surface peripheral grinding proces with the use of various design of experiment (DoE)") Mechanik, Vol. 91, No. 10 (2018): pages 929-931 Modelowanie sił w szlifowaniu obwodowym płaszczyzn według różnych planów badawczych WITOLD HABRAT MARCIN ŻÓŁKOŚ JANUSZ ŚWIDER ELŻBIETA SOCHA * The paper presents forces modeling with the use of DoE models, such as (Box-Wilson) central composite design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…e results of the experiments for the flat surface grinding process vibration conditions and force measurement have demonstrated that the higher values of grinding forces were obtained in the normal component (see Table 2) which concurs with the previous research findings in the literature [27,35]. It can be noted that, in the range of the cutting speed from 20 to 25 m/s and the depth of cut from 0.005 to 0.01 mm, the increase of the cutting speed and the depth of cut parameters is connected with an increase in the grinding forces and the amplitudes of vibration in both tangential and normal directions, but the grinding forces and vibrations grow more quickly in normal direction than in the tangential direction.…”
Section: Experimental Verificationsupporting
confidence: 90%
“…e results of the experiments for the flat surface grinding process vibration conditions and force measurement have demonstrated that the higher values of grinding forces were obtained in the normal component (see Table 2) which concurs with the previous research findings in the literature [27,35]. It can be noted that, in the range of the cutting speed from 20 to 25 m/s and the depth of cut from 0.005 to 0.01 mm, the increase of the cutting speed and the depth of cut parameters is connected with an increase in the grinding forces and the amplitudes of vibration in both tangential and normal directions, but the grinding forces and vibrations grow more quickly in normal direction than in the tangential direction.…”
Section: Experimental Verificationsupporting
confidence: 90%
“…The experiment (DoE) was planned in Design-Expert 13 software. One of the methods used in designing of experiments is the surface response method (RSM) -multicomponent research designs are based on it [28]. For the researches central composite face centered design (CCF) was applied for two dependent variables assuming levels of values ( 32 ) where α = 1.…”
Section: Methodsmentioning
confidence: 99%